Potentials of mountainous region of Serbia for map sector development - Turudija Živanović, Svetlana; Marković, Tatjana; Živanović, Tomislav (Economics of Agriculture, 2010)
Apart from mineral row material and energetic resources, soil quality, relief characteristics and hydro-potentials, natural resources also comprises for landscape characteristics as well as geographic position and biological diversity. Medicinal and aromatic plants (MAP) as a resource, is a component of the natural environment that may play an important role in structuring of spatial, social and economic rural areas that belong to mountainous region of Republic of Serbia. These areas are blessed with numerous resources (climate, soil, biodiversity, labour, etc) that are prerequisite for development of MAP sector, although they are not adequately utilised. Territory of Serbia, as a part of Balkan Peninsula, is one of the most important biodiversity centres and medicinal plants belong to economically the most signifcant ones in its flora. MAP sector encompasses production processing units, competent personnel as well as institutions that may support it and improve business on domestic market. MAP business is linked to certain regions of the country where the purchase is well organized: in the South-East part of Serbia collection of MAP has a long tradition, while in Vojvodina – there is a large-scale MAP production. General recommendations are: to increase surfaces under wild MAP collection within collection areas and to introduce large-scale MAP production in mountainous regions of Serbia. At the moment, there is no good concept of sustainable collection, processing and marketing in the MAP sector of Serbia.